Consumption of medium- and long-chain triacylglycerols decreases body fat and blood triglyceride in Chinese hypertriglyceridemic subjects - Xue, C; Liu, Y; Wang, J; Zhang, R; Zhang, Y; Zhang, J; Zheng, Z; Yu, X; Jing, H; Nosaka, N; Arai, C; Kasai, M; et al. (European journal of clinical nutrition, 2009)
Objectives: To investigate the effects of medium- and long-chain triacylglycerol (MLCT) on blood triglyceride (TG) in Chinese hypertriglyceridemic subjects. Methods: A double-blind controlled clinical trial was carried out, in which 112 subjects with hypertriglyceridemia were randomly divided into two dietary oil groups: (1) long-chain triacylglycerol (LCT) and (2) MLCT. All subjects were requested to ingest fixed energy and to continue their normal activity levels, and to consume LCT or MLCT oil at 25-30 g daily during the study period. Anthropometric measurements of body weight, body mass index (BMI), body fat, body fat percentage, waist and hip circumference (WC and HC), areas of subcutaneous and visceral fat by computed tomography scanning and blood biochemical markers were measured at the beginning and end of the study. Results: There were 50 and 51 subjects left in LCT and MLCT groups, respectively. There were no significant differences in daily intake of energy, protein, fat and carbohydrate, as well as the daily physical activity between the two groups during the study. After 8 weeks, MLCT group showed a significant decrease in body weight, BMI, WC, HC, ratio of WC and HC, body fat, body fat percentage and subcutaneous fat when compared with the initial values. The decrease in body weight, BMI, WC, body fat and subcutaneous and visceral fat was significantly greater in MLCT group than that in the LCT group. Furthermore, the serum concentrations of TG in MLCT group were significantly lower than those in the LCT group. Conclusions: Consumption of MLCT may reduce body weight, body fat and blood TG in hypertriglyceridemic subjects under an appropriate dietary regime.